Exploring mothers' experiences of perinatal care in Cyprus: Babies Born Better survey - E. Hadjigeorgiou; M. Andreaki; I. Koliandri; A. Spyridou; M. C. Balaam; A. Christoforou (BMC, 2023)
Abstract Introduction A positive perinatal experience facilitates a smooth transition to motherhood and enhances the development of a strong bond between mother and newborn, contributing to maternal and societal wellbeing. Given the medicalization of childbirth in Cyprus, the examination of mothers' experiences of perinatal care becomes imperative. Aim To investigate mothers' experiences of care during the perinatal period and to identify factors related to the provision of maternal care that contribute to the interpretation of these experiences. Methods The study draws on data from the European survey "Babies Born Better", an online survey utilizing a mixed-methods approach to explore women's experiences of maternity care across Europe. The study population were women who had given birth in Cyprus over a 5-year period (2013-2018). Quantitative data were analyzed using SPSS v22, while qualitative data were analyzed through inductive content analysis. Findings A total of 360 mothers participated in the study. In rating their overall experience, 24.2% stated that they had a "bad experience", 11.1% a "good experience",13.9% a "very good experience", and 13,3% a "very bad experience". The top three sub-factors of the overall experience which received positive evaluation were "Relationship with health care professionals" (33.6%), "Birth environment and care" (11.4%), and "Breastfeeding guidance" (10.8%). The qualitative analysis yielded five themes: "Relationship with health care professionals", "Breastfeeding establishment", "Childbirth rights", "Birth environment and services" and "Choice of mode of birth". Conclusion Mothers in Cyprus wish to have respectful maternity care. They need maternity health care professionals to respect their dignity and ask for evidence-based information with shared decision making. Mothers in Cyprus expect to have their childbirth rights safeguarded, to have better support from HCP, and to receive humanized care. The perinatal care provided in Cyprus needs significant improvements based on mothers' needs and expectations.